PENERAPAN AKUNTANSI DAN MANAJEMEN KEUANGAN PADA PENGATURAN KEUANGAN PRIBADI - Kusumadyahdewi, Kusumadyahdewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Manage of personal finance is very important, because many products and services offered in the market. We must more carefully to spend our money not fulfill what we want but what we need, Management for personal finance can adapted from accounting and Finance Management for corporation with adjustment. We must record income and outcome of our money as responsibility to our self and controlling our spiritual quotient, and then we can measure our achievement. Residual of our income can saved for the sudden need, or invest in many thing as our basic need, for example land and building or in portfolio, for future. This article discuss about how we apply accounting and finance management to personal finance management and also the application for personal finance in our gadget.Keywords: Accounting, Finance Management, Personal Finance Management